Global Repertoire of Human Antibodies Against Plasmodium falciparum RIFINs, SURFINs, and STEVORs in a Malaria Exposed Population - Kanoi, Bernard N.; Nagaoka, Hikaru; White, Michael T.; Morita, Masayuki; Palacpac, Nirianne M. Q.; Ntege, Edward H.; Balikagala, Betty; Yeka, Adoke; Egwang, Thomas G.; Horii, Toshihiro; Tsuboi, Takafumi; Takashima, Eizo (Frontiers in Immunology, 2020)
Clinical immunity to malaria develops after repeated exposure to Plasmodium falciparum parasites. Broadly reactive antibodies against parasite antigens expressed on the surface of infected erythrocytes (variable surface antigens; VSAs) are candidates for anti-malaria therapeutics and vaccines. Among the VSAs, several RIFIN, STEVOR, and SURFIN family members have been demonstrated to be targets of naturally acquired immunity against malaria. For example, RIFIN family members are important ligands for opsonization of P. falciparum infected erythrocytes with specific immunoglobulins (IgG) acquiring broad protective reactivity. However, the global repertoire of human anti-VSAs IgG, its variation in children, and the key protective targets remain poorly understood. Here, we report wheat germ cell-free system-based production and serological profiling of a comprehensive library of A-RIFINs, B-RIFINs, STEVORs, and SURFINs derived from the P. falciparum 3D7 parasite strain. We observed that > 98% of assayed proteins (n=265) were immunogenic in malaria-exposed individuals in Uganda. The overall breadth of immune responses was significantly correlated with age but not with clinical malaria outcome among the study volunteers. However, children with high levels of antibodies to four RIFINs (PF3D7_0201000, PF3D7_1254500, PF3D7_1040600, PF3D7_1041100), STEVOR (PF3D7_0732000), and SURFIN 1.2 (PF3D7_0113600) had prospectively reduced the risk of developing febrile malaria, suggesting that the 5 antigens are important targets of protective immunity. Further studies on the significance of repeated exposure to malaria infection and maintenance of such high-level antibodies would contribute to a better understanding of susceptibility and naturally acquired immunity to malaria.